2008
DOI: 10.1016/j.ultsonch.2007.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical analysis of sonochemical degradation of phenol and its chloro-derivatives

Abstract: Phenol and its chloro-derivatives contribute significantly to environmental pollution hazards due to their high degree of toxicity as well as improper disposal methods. Cavitation can be used successfully for degradation of phenolic compounds and the rates of degradation are dependent on the type of the primary pollutant in the system. In the present work, a theoretical explanation has been provided to explain the observed degradation trends of phenol and chlorophenols on the basis of concentration of the poll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 12 publications
2
19
0
Order By: Relevance
“…The high-volume use of phenols in the United States and their potential toxicity has led the U.S. Environmental Protection Agency (US EPA) to define them as priority pollutants [15]. Most countries specify the maximum allowable concentration of phenols in the effluent streams to be less than 1 mg/l [16], [17]. The legislations in the UAE limit the total phenols in industrial water discharged to the marine environment to 0.1 mg/l [18].…”
Section: Introductionmentioning
confidence: 99%
“…The high-volume use of phenols in the United States and their potential toxicity has led the U.S. Environmental Protection Agency (US EPA) to define them as priority pollutants [15]. Most countries specify the maximum allowable concentration of phenols in the effluent streams to be less than 1 mg/l [16], [17]. The legislations in the UAE limit the total phenols in industrial water discharged to the marine environment to 0.1 mg/l [18].…”
Section: Introductionmentioning
confidence: 99%
“…Bapat et al [93] introduced the interfacial phenomenon in explaining sonochemical degradation of phenol. They analyzed theoretically, the degradation of phenol and its chloro-derivatives produced by the reaction of CCl 4 and phenol.…”
Section: Sonochemical Methodsmentioning
confidence: 99%
“…The chemical stability of these compounds towards radical attack in the liquid phase was also discussed. It has been observed that, due to their higher hydrophobicity, chloroderivates were degraded much faster than the parent compounds [123].…”
Section: Contributions From the Studies With Chlorinated Compoundsmentioning
confidence: 99%